Prenatal Diagnosis of Microdeletions or Microduplications in the Proximal, Central, and Distal Regions of Chromosome 22q11.2: Ultrasound Findings and Pregnancy Outcome - Li, Shuyuan; Han, Xu; Ye, Mujin; Chen, Songchang; Shen, Yinghua; Niu, Jianmei; Wang, Yanlin; Xu, Chenming (Frontiers in Genetics, 2019)
Several recurrent microdeletions and microduplications in the proximal, central, and distal regions of chromosomal 22q11.2 have been identified. However, due to a limited number of patients reported in the literature, highly variable clinical phenotypes, and incomplete penetrance, the pathogenicity of some microdeletions/microduplications in 22q11.2 central and distal regions are unclear. Hence, the genetic counseling and subsequent pregnancy decision are extremely challenging, especially when they are found in structurally normal fetuses. Here, we reported 27 consecutive cases diagnosed prenatally with 22q11.2 microdeletions or microduplications by chromosomal microarray analysis in our center. The prenatal ultrasound features, inheritance of the microdeletions/microduplications, and their effects on the pregnancy outcome were studied. We found that fetuses with 22q11.2 microdeletions were more likely to present with structure defects in the ultrasound, as compared to fetuses with 22q11.2 microduplications. Both the prenatal ultrasound findings and the inheritance of the microdeletions/microduplications affected the parent’s decision of pregnancy. Those with structure defects in prenatal ultrasound or occurred de novo often resulted in termination of the pregnancy, whereas those with normal ultrasound and inherited from healthy parent were likely to continue the pregnancy and led to normal birth. Our study emphasized that proximal, central, and distal 22q11.2 deletions or duplications were different from each other, although some common features were shared among them. More studies are warranted to demonstrate the underlying mechanisms of different clinical features of these recurrent CNVs, thereby to provide more information for genetic counseling of 22q11.2 microdeletions and microduplications when they are detected prenatally.